Fasilitasi Penyusunan Strategi Optimalisasi Potensi Wisata di Desa Mamigang Kabupaten Balangan - Wirawan; Hidayah, Sri; Fitri, Ahmad Azriel Iedil; Ilmi, Muhammad Ibnu Zainal; Aulia; Salsabella; Sriwahyuni, Dewi; Azizah, Azzahra Nur; Syifa, Noor; Baiti, Noor; Tsuraya, Ghaida Nur (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2025)
Mamigang Village in Halong District, Balangan Regency, South Kalimantan, has natural resources in the form of rivers, mountains, and waterfalls. Mamigang Village utilizes these natural resources as tourist attractions. However, the tourism sector has not been optimally managed, as it faces obstacles in infrastructure development, accessibility, and facilities. Additionally, other potential areas, such as culture, have not been utilized as part of tourism. The factors hindering tourism development include the abundance of tourist attractions and the confusion among tourism managers in developing tourism. Therefore, the community service team designed and implemented the program “Creation of a Master Plan Book for Mapping Potential and Developing Tourism Strategies in Mamigang Village.” This community service program uses the live-in method in the village for 56 days, which runs from July 17, 2025, to September 10, 2025. This program consists of several activities, namely: 1) Program socialization and perception alignment; 2) Creation of a master plan book design; 3) Field surveys; 4) Field data analysis; 5) Compilation of a master plan book for mapping potential and tourism development strategies; and 6) Discussion of SWOT results and dissemination of results. The results achieved from this community service program are the compilation of a master plan book mapping the potential and strategies for tourism development. The book contains tourism development strategies analyzed based on the potential, obstacles, challenges, and opportunities of existing tourist attractions. Furthermore, it is hoped that this program will have a long-term impact through the optimal development of tourism, which can improve the local community's economy. Furthermore, increasing awareness of the natural and cultural wealth in Mamigang Village can become a local-based potential.